FRIENDSHIP IN THE THREE MUSKETEERS: A THEMATIC, STRUCTURAL, AND CHARACTER ANALYSIS - Romaito Marbun; Charli Marbun; Bella Renata Manalu; Nurhayati Purba (Jurnal Intelek Insan Cendikia, 2025)
This research delves into the themes of friendship and loyalty within Alexandre Dumas’s The Three Musketeers through a nuanced qualitative literary analysis. By scrutinizing the narrative architecture, character arcs, and thematic motifs, the research seeks to illuminate how Dumas elevates friendship from mere personal affection to a noble moral ideal. The primary reference is the English translation by Pevear (2006), complemented by an array of scholarly discourse on Dumas’s oeuvre and theoretical perspectives on friendship. Employing three analytical approaches, namely, thematic analysis to uncover persistent values of loyalty, structural analysis to examine how the narrative structure underscores the importance of camaraderie, and character development analysis to trace the growth of pivotal figures, the research demonstrates that friendship in the novel is depicted as a virtue rooted in mutual respect, moral integrity, and self-sacrifice. Dumas masterfully employs this motif not only to propel the storyline but also to critique authority and extol ethical resistance. Ultimately, the research reveals friendship as a dynamic force with profound personal and political significance, elevating it to a moral and societal ideal